Impact on Health‐Related Quality of Life of Parenteral Nutrition for Patients with Advanced Cancer Cachexia: Results from a Randomized Controlled Trial. (25th March 2020) - Bouleuc, Carole; Anota, Amélie; Cornet, Cécile; Grodard, Ghislain; Thiery‐Vuillemin, Antoine; Dubroeucq, Olivier; Crétineau, Nathalie; Frasie, Véronique; Gamblin, Vincent; Chvetzoff, Gisèle; Favier, Laure; Tournigand, Christophe; et al.
Abstract: Background: Malnutrition worsens health‐related quality of life (HRQoL) and the prognosis of patients with advanced cancer. This study aimed to assess the clinical benefits of parenteral nutrition (PN) over oral feeding (OF) for patients with advanced cancer cachexia and without intestinal impairment. Material and Methods: In this prospective multicentric randomized controlled study, patients with advanced cancer and malnutrition were randomly assigned to optimized nutritional care with or without supplemental PN. Zelen's method was used for randomization to facilitate inclusions. Nutritional and performance status and HRQoL using the European Organization for Research and Treatment of Cancer QLQ‐C15‐PAL questionnaire were evaluated at baseline and monthly until death. Primary endpoint was HRQoL deterioration‐free survival (DFS) defined as a definitive deterioration of ≥10 points compared with baseline, or death. Results: Among the 148 randomized patients, 48 patients were in the experimental arm with PN, 63 patients were in the control arm with OF only, and 37 patients were not included because of early withdrawal or refused consent. In an intent to treat analysis, there was no difference in HRQoL DFS between the PN arm or OF arm for the three targeted dimensions: global health (hazard ratio [HR], 1.31; 95% confidence interval [CI], 0.88–1.94; p = .18), physical functioning (HR, 1.58; 95% CI, 1.06–2.35; p = .024), and fatigue (HR, 1.19; 95% CI, 0.80–1.77; p = .40); there was a negative trend for overall survival among patients in the PN arm. In as treated analysis, serious adverse events (mainly infectious) were more frequent in the PN arm than in the OF arm ( p = .01). Conclusion: PN improved neither HRQoL nor survival and induced more serious adverse events than OF among patients with advanced cancer and malnutrition. Clinical trial identification number . NCT02151214 Implications for Practice: This clinical trial showed that parenteral nutrition improved neither quality of life nor survival and generated more serious adverse events than oral feeding only among patients with advanced cancer cachexia and no intestinal impairment. Parenteral nutrition should not be prescribed for patients with advanced cancer, cachexia, and no intestinal failure when life expectancy is shorter than 3 months. Further studies are needed to assess the useful period with a potential benefit of artificial nutrition for patients with advanced cancer. Abstract : Malnutrition impairs clinical outcome in patients with advanced cancer. This study compared parenteral nutrition with oral feeding for malnourished patients with advanced cancer and functional gastrointestinal tract.